The mental health of seafarers: a brief review - Robert T. B. Iversen (Актуальні проблеми транспортної медицини, 2011)
This report discusses the mental health of seafarers from two separate but related aspects. The first is a brief review of statistics on seafarers’ mental health and the underlying causes of poor mental health by many seafarers. Statistics show that the rate of suicide by seafarers is much higher than general populations and that the causes of depression leading to suicide include loneliness, separation from families, stress, lack of shore leave, short ship turn abound times, job security and cultural problems. The second is a description of two projects started in the past three years by the Rotary Club of Melbourne South (Australia) and by the International Committee on Seafarers Welfare (ICSW). The Rotary project, being carried out under the guidance of the Melbourne Port Welfare Association, has distributed booklets on the single topic of depression for Masters and leaflets for non-officer seafarers in four languages: English, Chinese, Tagalog and Russian. As of June 1, 2011 this material has been put aboard more than 1,200 ships in five ports in Australia. The ICSW project has produced guidelines in English for mental care onboard merchant ships and covers stress, harassment and bullying, anxiety, depression, disruptive thinking and behavior and addiction to alcohol and drugs. The Rotary Club of Melbourne South has started planning for the First International Symposium on the Mental Health of Seafarers to be held in either Hong Kong or Singapore in early 2013.